China's international student recruitment as 'outward-oriented' higher education internationalisation: an exploratory empirical inquiry. Issue 4 (4th July 2019) - Wu, Hantian
Abstract: This study investigates China's international student recruitment strategy and policies as a dimension of its present approach of using higher education internationalisation for soft power and image enhancement. An exploratory survey of international graduate students in English instruction programmes in education-related majors in three Chinese universities has been conducted to analyse their attitudes towards China's approach. Quantitative analysis has been conducted on the survey data based on Holmes's four-pattern taxonomy for analysing contextual features, which includes normative patterns, sociological laws, national conditions, and deep cultural roots. Qualitative data have been collected and analysed as a supplement. This study attempts to reveal the relations between international students' source-country contextual features, identified based on Holmes's taxonomy, and their attitudes towards China's approach in international student recruitment. Policy suggestions are provided based on these findings.